Narratives of healing through traditional medicinal knowledge in Indonesian folklore - Zamruddin, Mardliya Pratiwi; Prafitri, Wilma (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This research examines the intricate relationship between oral traditions and indigenous healing practices across Indonesia. This study uses  Java, Bali, Kalimantan and Sulawesi folktales to examine how myths, legends and ritual narratives encode traditional medicinal knowledge. These stories reveal a comprehensive view of health as a  harmony across physical, spiritual, and environmental realms. Through thematic and symbolic analysis, the study shows ethnobotanical ideas, the sociocultural logic of healing, and the narrative roles of herbal cures and traditional healers. Folklore provides therapeutic knowledge, an ecological ethic and moral compass that helps societies live sustainably and pass down information. The study contributes to worldwide discussions on intangible cultural heritage and knowledge system decolonization by placing these tales in cultural and public health contexts. It concludes that folklore is a living repository of medical epistemologies and a significant resource for culturally grounded health discourse in Indonesia and beyond.